Energy Transport by Radiation in Hyperbolic Material Comparable to Conduction. (9th December 2019) - Salihoglu, Hakan; Iyer, Vasudevan; Taniguchi, Takashi; Watanabe, Kenji; Ye, Peide D.; Xu, Xianfan
Abstract: Radiation as a heat transfer mode inside a bulk material is usually negligible in comparison to conduction. Here, the contribution of radiation to energy transport inside a hyperbolic material, hexagonal boron nitride (hBN), is investigated. With hyperbolic dispersion, i.e., opposite signs of dielectric components along principal directions, phonon polaritons contribute significantly to energy transport due to a much greater number of propagating modes compared to that in a normal material. A many‐body model is developed to account for radiative heat transfer in a material with a nonuniform temperature distribution. The total radiative heat transfer through hBN is found to be largely contributed by the high‐κ modes within the Reststrahlen bands, and is comparable to phonon conduction. Experimental measurements of temperature‐dependent thermal transport also show that radiative contribution to thermal transport is of the same order as that from phonons. Therefore, this work shows, for the first time, radiative heat transfer inside a material can be comparable to phonon conductive heat transfer. Abstract : Energy transport by electromagnetic waves inside hyperbolic material boron nitride is investigated. A microscopic many‐body model is developed and shows that radiative heat transfer is in the same order of magnitude as phononic heat transfer. Experiments on total thermal transport provide the same conclusion, and radiative transfer accounts for a larger fraction of total energy transport at higher temperatures.